2017
DOI: 10.20944/preprints201708.0009.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subterranean Karst Environments as a Global Sink for Atmospheric Methane

Abstract: Abstract:The air in subterranean karst cavities is often depleted in methane (CH4) relative to the atmosphere. Karst is considered a potential sink for the atmospheric greenhouse gas CH4 because its subsurface drainage networks and solution-enlarged fractures facilitate atmospheric exchange. Karst landscapes cover about 14 % of earth's continental surface, but observations of CH4 concentrations in cave air are limited to localized studies in Gibraltar, Spain, Indiana (USA), Vietnam, Australia, and by incomplet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…For example, microalgae in Atacama Desert coastal caves produce oxygen as a photosynthetic byproduct (Azua‐Bustos et al., 2009, 2010), while Webster et al. (2015) and Webster (2019) have shown that chemical and isotopic constituents in cave air are distinguishable from the surrounding ambient air. While this approach seems promising, more research will be required to examine other gases (e.g., methane, hydrogen, and carbon monoxide; Lyu et al., 2018; Voordouw, 2002; Wang & Wan, 2009) produced by different microbial metabolisms.…”
Section: Resultsmentioning
confidence: 99%
“…For example, microalgae in Atacama Desert coastal caves produce oxygen as a photosynthetic byproduct (Azua‐Bustos et al., 2009, 2010), while Webster et al. (2015) and Webster (2019) have shown that chemical and isotopic constituents in cave air are distinguishable from the surrounding ambient air. While this approach seems promising, more research will be required to examine other gases (e.g., methane, hydrogen, and carbon monoxide; Lyu et al., 2018; Voordouw, 2002; Wang & Wan, 2009) produced by different microbial metabolisms.…”
Section: Resultsmentioning
confidence: 99%